A PRAGMATIC STUDY OF SPEECH ACTS IN POLITICAL DISCOURSES: BAHLIL LAHADALIA’S RHETORIC ON BBM PRICES - Agnes Dhea Oktavia Sinaga; Sarah Anastasia; Tria Amelia Surbakti; Isnaila Ramadhani; Zsa Zsa Adelia Attaqiyyah; Dian Marisha Putri (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study aims to analyze the use of speech acts in the statements of Bahlil Lahadalia regarding thefuel price increase (BBM) policy. This research employs a qualitative approach within the frameworkof pragmatics, focusing on speech act theory. The data were collected from Bahlil Lahadalia’s publicstatement delivered on April 20, 2026, which addresses the government's position on the BBM issue.The data were analyzed by identifying and classifying the locutionary, illocutionary, andperlocutionary acts found in the statements. The findings reveal that various types of speech acts arepresent in the data, with illocutionary acts playing a dominant role in conveying intentions such asasserting information, justifying policies, and responding to public concerns. These illocutionaryforces consist of assertive (4 instances), directive (2 instances), commissive (1 instance), expressive (1instance), and declarative (1 instance) acts. Locutionary acts function to deliver the literal meaning ofthe statements, while perlocutionary acts reflect the potential effects on the audience, particularly inshaping public perception and response. The analysis also shows that the use of these speech acts inpolitical discourse is strategic and purposeful. Consequently, this study indicates that Lahadalia’sstatements on the BBM issue perform specific communicative actions that convey meaning, intention,and influence. This research contributes to the understanding of how language is used in politicalcommunication, especially in addressing sensitive socio-economic issues.Keywords: Bahlil Lahadalia, BBM policy, political discourse, pragmatics, speech acts